2016
DOI: 10.18632/oncotarget.8913
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of the miR-483-3p overcomes the miR-145/TP53 pro-apoptotic loop in hepatocellular carcinoma

Abstract: The miR-145-5p, which induces TP53-dependent apoptosis, is down-regulated in several tumors, including hepatocellular carcinomas (HCCs), but some HCCs show physiological expression of this miR. Here we demonstrate that in HCC cells carrying wild-type TP53 the steady activation of the miR-145 signaling selects clones resistant to apoptosis via up-regulation of the oncogenic miR-483-3p. Expression of the miR-145-5p and of the miR-483-3p correlated negatively in non-neoplastic liver (n=41; ρ=−0.342, P=0.028), but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…Anti-p21 (MS-891-B Thermo Scientific) Western Blot was performed on cell extracts as described [49] using BT20 cells exposed to 9 × 10 −6 m protein for 4 h. Fold increase of p21 was referred to a β-actin control. Sections were incubated with 10% normal goat serum (NGS) in antibody diluent (1% BSA in 100 × 10 −3 m Tris buffer) and then of 1:100 dilution of anti-p21 antibody (M 7202, Dako, Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Anti-p21 (MS-891-B Thermo Scientific) Western Blot was performed on cell extracts as described [49] using BT20 cells exposed to 9 × 10 −6 m protein for 4 h. Fold increase of p21 was referred to a β-actin control. Sections were incubated with 10% normal goat serum (NGS) in antibody diluent (1% BSA in 100 × 10 −3 m Tris buffer) and then of 1:100 dilution of anti-p21 antibody (M 7202, Dako, Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, this study also demonstrated that miR‐483‐5p could promote IGF2 transcription in turn by enhancing the RNA helicase DHX9 associated with the IGF2 transcript. For miR‐483‐3p, it has been reported dysregulated in multiple cancers, implying it could participate in regulating cell functions, such as growth and apoptosis 38, 39…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SET overexpression was proven to be a common alteration in early-stage CRC, promoting cell migration and EMT in CRC cells (Cristóbal et al, 2019). The miR-145-5p was downregulated in several tumors, including hepatocellular carcinomas, via p53 pathway apoptosis (Lupini et al, 2016). However, the posttranscriptional regulation role of miR-145-5p in CRC through SET has not yet been found.…”
Section: Discussionmentioning
confidence: 99%